Research training and undergraduate thesis for a degree in education - Núñez Flores, María Isabel (2014)
and information, globalization and postmodernity in which positions the university today. It is assumed complex social nature of education and the challenges of quality demanded by the labor market, and that research is the necessary path for the development of capabilities that allow to efficiently and effectively address the changes that occur advances of science and technology, as well as professional improvement and their contribution to socioeconomic development. Is negligible percentage of undergraduate theses conducted in the present decade, before the final Class. Formulate the problem: What is the impact of research training in the choice of thesis in Education UNMSM? In addition to time and financial investment. The sample constitutes 60 students X cycle of the specialties at the School of Education Academic Professional UNMSM. The results will guide the methodological and strategic decision to increase the choice of the thesis.